MENTORING THE DEVELOPMENT PROGRAM OF MADRASAH DINIYAH TAKMILIYAH IN DUSUN MANDALAGIRI, CISONTROL, RANCAH DISTRICT, CIAMIS - Ruminda Ruminda; Widiati Isana (Politeknik Negeri Jakarta, 2025)
Madrasah Diniyah Takmiliyah (MDT) is a non-formal Islamic educational institution that has important and comprehensive roles in creating Islamic generations. The existence of MDT in an area is expected to be able to reastore the faded Islamic values in terms of spirituality, morality, and harmony. MDT At-Taqwa and MDT Miftahussa'adah in Mandalagiri Village, Cisontrol, Rancah, Ciamis, are two of the large number of madrasas that still need assistance in implementing madrasah development programs to a betterdirection. This is due to the current condition of the two madrasas, they do not yet have a Madrasah Diniyahcurriculum that is in accordance with the Ministry of Religion standards, there is no sustainable learning pattern, the long and short-term activity programs are not yet arranged, the welfare of teachers is still minimal, and the administration and infrastructure facilities are not yet complete in the process of teachingand learning activities. Given these problems, the assistance of this preparation program was carried out asan effort to improve the development program of the two MDTs in understanding the curriculum, teaching patterns, program activities, and the welfare of madrasa teachers. The assistance provided is the preparation of the MDT development program through internal strengthening, curriculum and secretarial administration. The method used in this program is ABCD (Asset Based Community-driven Development). The results obtained from this activity are the improved of MDT management, MDT assistance in curriculumimplementation, and the increase in madrasa administration management.